A bright new page in portable displays. - Crawford, G.P (IEEE spectrum)
Wouldn't it be a lot easier to read a laptop's screen if the words looked as if they were printed on paper, as in a newspaper or magazine? Well, that is the case for a trio of unique displays about to hit the market. Of the three new displays, the closest to hitting the market is a liquid-crystal display (LCD) from Kent Displays Inc., Kent, Ohio. Called cholesteric because the liquid-crystal material it uses was originally derived from animal cholesterol, this LCD will be a full-color screen. The other two displays are based on entirely new concepts of how an electronic screen should work. One is the Gyricon from Xerox Corp.'s Pale Alto Research Center (PARC) in California, which can be rolled up into long sheets and cut by designers to fit the application. E Ink, the third type of display, is being developed by the eponymous E Ink Inc., a Cambridge-based spin-off of the Massachusetts Institute of Technology (MIT). Even thinner than the Gyricon, it uses small transparent spheres filled with a liquid blue dye in which white chips float